Penilaian Bangunan dalam Rangka Pengawasan Kegiatan Membangun Sendiri - Ferry Irawan; Bayu Achmadi; Eri Wahyudi (Universitas Pamulang, 2021)
This study aims to understand the building valuation process in order to supervise self-building activities at KPP Pratama Mojokerto and its suitability with regulations. In addition, this research is conducted to determine the obstacles faced during the building valuation process at KPP Pratama Mojokerto and the solution to these problems. The object in this research is the valuation of warehouse buildings carried out by KPP Pratama Mojokerto in 2019. The building valuation aims to test compliance with VAT on self-building activities (KMS). The valuation uses a cost approach. The appraiser uses the new reproduction cost method and the unit in placed technique to determine the cost of building a warehouse. The valuation is carried out based on the applicable valuation regulations at the time of the valuation, including SE-61/PJ/2015, SE-54/PJ/2016, and the Indonesian Valuation Standard (SPI). The result of the valuation is the market value of the light steel warehouse building when it is completed by the taxpayer PT ABC. This research contributes to the calculation basis of VAT. Keywords: VAT; Valuation; Self-Building Activities